Service Sector Reform and Manufacturing Productivity : Evidence from Indonesia - Duggan, Victor (World Bank, Washington, DC, 2013)
This paper examines the extent to which policy restrictions on foreign direct investment in the Indonesian service sector affected the performance of manufacturers over the period 1997-2009. It uses firm-level data on manufacturers' total factor productivity and the OECD's foreign direct investment Regulatory Restrictiveness Index, combined with data from Indonesia s input-output tables regarding the intensity with which manufacturing sectors use services inputs. Controlling for firm-level fixed effects and other relevant policy indicators, it finds, first, that relaxing policies toward foreign direct investment in the service sector was associated with improvements in perceived performance of the service sector. Second, it finds that this relaxation in service sector foreign direct investment policies accounted for 8 percent of the observed increase in manufacturers' total factor productivity over the period. The total factor productivity gains accrue disproportionately to those firms that are relatively more productive, and that gains are related to the relaxation of restrictions in both the transport and electricity, gas, and water sectors. Total factor productivity gains are associated, in particular, with the relaxation of foreign equity limits, screening, and prior approval requirements, but less so with discriminatory regulations that prevent multinationals from hiring key personnel abroad.